A role for TASK2 channels in the human immunological synapse. Issue 2 (18th December 2020) - Fernández‐Orth, Juncal; Rolfes, Leoni; Gola, Lukas; Bittner, Stefan; Andronic, Joseph; Sukhorukov, Vladimir L.; Sisario, Dmitri; Landgraf, Peter; Dieterich, Daniela C.; Cerina, Manuela; Smalla, Karl‐Heinz; Kähne, Thilo; et al.
Abstract: The immunological synapse is a transient junction that occurs when the plasma membrane of a T cell comes in close contact with an APC after recognizing a peptide from the antigen‐MHC. The interaction starts when CRAC channels embedded in the T cell membrane open, flowing calcium ions into the cell. To counterbalance the ion influx and subsequent depolarization, Kv 1.3 and KCa3.1 channels are recruited to the immunological synapse, increasing the extracellular K + concentration. These processes are crucial as they initiate gene expression that drives T cell activation and proliferation. The T cell‐specific function of the K2P channel family member TASK2 channels and their role in autoimmune processes remains unclear. Using mass spectrometry analysis together with epifluorescence and super‐resolution single‐molecule localization microscopy, we identified TASK2 channels as novel players recruited to the immunological synapse upon stimulation. TASK2 localizes at the immunological synapse, upon stimulation with CD3 antibodies, likely interacting with these molecules. Our findings suggest that, together with Kv 1.3 and KCa3.1 channels, TASK2 channels contribute to the proper functioning of the immunological synapse, and represent an interesting treatment target for T cell‐mediated autoimmune disorders. Abstract : The immunological synapse (IS) is crucial as it determines T cell activation and proliferation. Not only CRAC, Kv1.3 and KCa3.1 channels are recruited but also TASK2 channels are novel players that contribute to the correct functioning of the IS.